Structural diversity as a reliable and novel predictor for ecosystem productivity. Issue 1 (1st February 2023) - LaRue, Elizabeth A; Knott, Jonathan A; Domke, Grant M; Chen, Han YH; Guo, Qinfeng; Hisano, Masumi; Oswalt, Christopher; Oswalt, Sonja; Kong, Nicole; Potter, Kevin M; Fei, Songlin
Abstract : The physical structure of vegetation is thought to be closely related to ecosystem function, but little is known of its pertinence across geographic regions. Here, we used data from over three million trees in continental North America to evaluate structural diversity – the volumetric capacity and physical arrangement of biotic components in ecosystems – as a predictor of productivity. We show that structural diversity is a robust predictor of forest productivity and consistently outperforms the traditional measure – species diversity – across climate conditions in North America. Moreover, structural diversity appears to be a better surrogate of niche occupancy because it captures variation in size that can be used to measure realized niche space. Structural diversity offers an easily measured metric to direct restoration and management decision making to maximize ecosystem productivity and carbon sequestration.